SISTEM APLIKASI PEMBAYARAN SISWA MENGGUNAKAN BAHASA PEMROGRAMAN VISUAL BASIC 6.0 - Matsna Agustina Rosyida; Siti Sufaidah; Tholib Hariono (SAINTEKBU, 2018)
Madrasah is an educational institution under the auspices of the Education Department which is moving in the field of school services. Madrasahs that are still manual in handling activities such as recording payment transactions and reporting, manual here in the sense that there is no system that is integrated between parts. Manual record-keeping and reporting are irrelevant or out of date with the fast-paced, precise and accurate progress of the times. Therefore the need for a transition from a manual system to a computerized system. The computerized system to be created should be tailored to the needs of the madrasah. In this research, the writer tries to build madrasah payment system with the database so that it becomes better payment system, effective and efficient and help solve problems faced by the institution in Madrasah Aliyah Negeri Kandangan Office Kediri Regency related to the payment system (like reporting and print receipt). In this case, the database will be used is Access, While the programming using Visual Basic 6.0. In this study discussed the test of the program that has been made. It aims to determine the extent to which the exact execution of programs that have been made and did not rule out knowing weaknesses. So it can be concluded that the program created can run correctly and in accordance with what is expected. Whereas with the construction of this Madrasah Payment Application Sistem, problems in making payment data such as reporting and proof of payment (Receipt) can provide convenience for the officers. Also with database utilization, payment data will be saved automatically. Keywords: Access, Visual Basic 6.0, Student Payout.